High concentration of estradiol has a negative correlation with free thyroxine during the second trimester of pregnancy. Issue 10 (26th September 2022) - He, Leqi; Li, Xiaoying; Chen, Zaoping; Wang, Wei; Wang, Kai; Huang, Xinmei; Yang, Qian; Ke, Wencai; Liu, Jun; Zha, Bingbing
Abstract : Objective: To explore the relationship between estradiol (E2) and thyroid function during the second trimester of pregnancy and the effect of E2 on sodium iodide transporter (NIS) expression in cultured thyroid cells. Materials and methods: We analyzed relationships between E2 and thyroid function in 196 pregnant women during the second trimester. Multiple linear regression analysis was performed between E2 and thyroid function. The human thyroid Nthy-ori3-1 cells were cultured in different E2 concentrations, and the mRNA levels of NIS, estrogen receptor (ER)-α, and ER-β were measured by quantitative real-time PCR. Their protein levels were assessed by western blot. Results: E2 was positively correlated with thyroid-stimulating hormone (TSH) and negatively correlated with free thyroxine (FT4) ( P  < 0.05). When we corrected for age, BMI, alanine aminotransferase, and serum creatinine, E2 was still negatively correlated with FT4 ( P  < 0.5) during the second trimester. In Nthy-ori3-1 cells treated with 10 nM E2, NIS and ER-β mRNA levels were significantly reduced, while ER-α mRNA level was not altered ( P  > 0.5). Moreover, 10 nM E2 significantly decreased protein levels of ER-β, phosphorylated versions of protein kinase A (p-PKA), phosphorylated versions of cAMP response element-binding protein (p-CREB), and NIS, while treatment with the ER-β inhibitor restored the expression of p-PKA, p-CREB, and NIS ( P  < 0.05). Conclusion: High concentration of E2 has a negative correlation with FT4. High concentration of E2 can inhibit the NIS expression through the ER-β-mediated pathway, which may cause thyroid hormone fluctuations during pregnancy.